Change management in the digital economy: Model proposal - Geada, N. (International Journal of Innovation in the Digital Economy, 2020)
The digital economy shows a great potential of growth, in the scope of the individuals and in transactions between companies. The internet is the great driving force behind this transition. Therefore, the impacts of change have on the economic environment of organizations can only be balanced when implementing good practices and control mechanisms, considering the critical factors for the success of implementation of change using methodologies versus technology versus resources. The control of digital change focuses on the constant need to adapt methodologies in the most varied application scenarios, and in its control in a structured way, namely a simple way to succinct this concept, so it is possible to affirm that the digital economy correlates directly with the constant need for change. Therefore, the objective is through a model proposal to support for the change management that allows managing the processes and associated impacts.